Interspecific Cross-Mating Between Aedes aegypti and Aedes albopictus Laboratory Strains: Implication of Population Density on Mating Behaviors. - P, Marcela; Hassan, AA; Hamdan, A; Dieng, H; Kumara, TK (PubMed, 2015)
Mating behavior between Aedes aegypti and Ae. albopictus, established colony strains were examined under laboratory conditions (30-cm(3) screened cages) for 5 consecutive days. The effect of selected male densities (30, 20, 10) and female density (20) on the number of swarming, mating pairs, eggs produced, and inseminated females were evaluated. Male densities significantly increased swarming behavior, mating pairs, and egg production of heterospecific females, but female insemination was reduced. Aedes aegypti males mate more readily with heterospecific females than do Ae. albopictus males. The current study suggests that Ae. aegypti males were not species-specific in mating, and if released into the field as practiced in genetically modified mosquito techniques, they may mate with both Ae. aegypti and Ae. albopictus females, hence reducing populations of both species by producing infertile eggs.